Sequential Microwave-Ultrasound Assisted Extraction of Flavonoid from Moringa oleifera: Product Characteristic, Antioxidant and Antibacterial Activity - Aji Prasetyaningrum; Bakti Jos; Ratnawati Ratnawati; Nur Rokhati; Teguh Riyanto; Gian Restu Prinanda (Universitas Gadjah Mada, 2022)
Moringa oleifera leaves contain secondary metabolites in flavonoid compounds known to prevent several diseases. Therefore, appropriate extraction methods are required to produce extracts with a high yield of flavonoids from Moringa. In this study, the extraction from Moringa leaves was carried out using the sequential microwave/ultrasound-assisted extraction (MUAE) method compared with sequential ultrasound/microwave (UMAE), microwave (MAE), ultrasound (UAE), and maceration (ME). The effects of the time, temperature, and percentage of ethanol were studied on total flavonoid content using AlCl3 colorimetric assay. The extracts were analyzed by Scanning Electron Microscopy (SEM), Fourier Transforms Infrared Spectrophotometry (FTIR), and High-Performance Liquid Chromatography (HPLC). The antioxidant and antibacterial activities were tested using DPPH-scavenging and disc diffusion methods. The results of SEM surface analysis on various extraction methods show differences on each surface. The FTIR spectrum showed the presence of flavonoid O–H at 3200 cm–1, C=O at 1621 cm–1, and C–O at 1019 cm–1. In the results of HPLC, MUAE extracts 16.70 mg/ 100 g flavonoid quercetin at the retention time of 4.5 min, with the highest total flavonoids (2.89 mg QE/g), the highest antioxidant activity (IC50 72.31 µg/mL), and highest antibacterial activity (S. aureus 7 mm, E. coli 2 mm).